Efeito do extrato de Ginkgo biloba L., Ginkgoaceae, na osteoporose induzida em ratas Wistar - Oliveira, Tânia T. de; Lucinda, Leda M. F.; Vieira, Beatriz J.; Salvador, Pollyanna A.; Peters, Vera M.; Reis, João E. de P.; Guerra, Martha de O. (Revista Brasileira de Farmacognosia, 2010)
Este trabalho investigou os efeitos do tratamento por vinte dias com extrato de Ginkgo biloba (EGb) na osteoporose induzida por glicocorticóides. Foram utilizadas 36 ratas divididas em seis grupos (n=6): Controle, osteoporose, controle positivo, EGb1 (14 mg EGb/mg/kg/dia), EGb2 (28 mg EGb/kg/dia) e EGb3 (56 mg EGb/kg/dia). Os tratamentos foram realizados por vinte dias, após a indução da osteoporose. Após a eutanásia foram removidos o fêmur e a mandíbula de todos os animais. A mandíbula esquerda foi radiografada digitalmente para avaliação da cortical e do suporte ósseo periodontal (SOP). A análise histomorfométrica foi realizada no fêmur e mandíbula direitos. O grupo controle foi comparado ao grupo osteoporose (Teste t de Student) e os demais grupos foram submetidos a ANOVA, seguido do teste post-hoc de Dunnett. Houve redução significava do SOP mesial, percentual ósseo alveolar (POA) mandibular, percentual ósseo trabecular (POT) do fêmur no grupo osteoporose. Houve aumento do SOP mesial no grupo controle positivo, EGb2 e EGb3. O POA da mandíbula e o POT do fêmur aumentaram nos grupos EGb2 e EGb3. O EGb nas doses de 28 mg/kg e 56 mg/kg recuperou de forma significativa o SOP mesial, o POA da mandíbula e o POT do fêmur.

The objective of this study was to investigate the effect of a 20 day treatment with extract of Ginkgo biloba (EGb) in glucocorticoid-induced-osteoporosis. 36 rats were divided into six groups (n=6): control, osteoporosis, positive control, EGb1 (14 mg EGb/kg/day), EGb2 (28 mg EGb/kg/day) and EGb3 (56 mg EGb/kg/day). Treatments were conducted for twenty days, after osteoporosis was induced. Following euthanasia the femur and mandible of all animals were removed. The left mandible was radiographed to evaluate the cortical and the periodontal bone support (PBS). The histomorphometric analysis was performed on the right mandible and the right femur. The control group was compared with the osteoporosis group (Student's t-test). The other groups were analyzed through ANOVA test followed by Dunnett post-hoc test. There was a significantly reduction in the mesial PBS, in the percentage of the alveolar bone (PAB) of the mandible and percentage of the trabecular bone (PTB) of the femur in the osteoporosis group. There was an increase in the mesial PBS in the positive control group, EGb2 and EGb3. The PAB of the mandible and the PTB of the femur increased in the EGb2 and EGb3 groups. The EGb in the 28 mg/kg and 56 mg/kg doses were effective to increase the mesial PBS, the PAB of the mandible and the PTB of the femur.
Keywords: Ginkgo biloba; Osteoporose; Radiografia; Histomorfometria; Alendronato de sódio; Ratos